PENAFSIRAN AYAT ETIKA BERTAMU DALAM KITAB RAWĀ´I’U AL-BAYĀN DAN KONTEKSTUALISASINYA DI INDONESIA - Ahmad Syahid (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2021)
Muslim believers have the duty to glorify guests, respect them with proper respect, because these are in accordance with Islamic sharia. Because with mutual respect, harmony will be created between a guest and the host. The purpose of this study is to find out how the ethics of visiting based on Islamic law contained in the interpretation of the visiting verses by al-Ṣābūnī in the book Rawā´i’u al-Bayān and its contextualisation in Indonesia. This research uses a thematic approach. Judging from the type, this research includes library research. The results of this study provide an explanation that a Muslim when going to visit must have ethics or morals. For those who are visiting you should say their greetings before entering, prioritize new greetings asking for permission, do not visit just any time, and do not do things that bother guests. For hosts who have guests, they should answer greetings with a better and give the same rights and treatment to guests without discriminating.